Quo Vadis German Scholarly Communication in Economics? - Athanasios Mazarakis; Isabella Peters (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this paper we study the situation of scholarly communication in Economics and Business Studies in Germany. We combine findings from an online survey, focus group interviews and a panel discussion. Some of the results of the survey are that economists at German universities and research institutes most frequently use the online encyclopedia Wikipedia, content sharing services, video and image hosting services as well as video conferencing systems. In a professional context, economists primarily use highly specialized tools such as learning management and reference management systems. Almost one in three German economists is active in academic and professional networks such as ResearchGate or Xing (Siegfried et al. 2015). Focus group interviews and panel discussion reveal that social media content and platforms are mainly used passively but acknowledged for serendipitously finding interesting research papers. They are also valuable for staying up-to-date on the discussion of current economic issues. Scholarly communication and scientific discourse with colleagues from Economics and Business Studies does, however, not yet take place essentially on social media platforms.
Conference: The Future of Scholarly Communication in Economics, Workshop, 30-31 March 2015, Hamburg
Keywords: A11; I23; 330; scholarly communication; social media; usage behaviour; Germany